A novel method for producing electron transparent films of interfaces between cells and biomaterials - Detsch, Rainer; et al. (Journal of Materials Science: Materials in Medicine, 2008)
Transmission electron microscopy (TEM) investigations of intact interfaces of cells and brittle biomaterials have proven difficult using common TEM preparation techniques. This paper describes a technique to fabricate thin sections for TEM investigation of intact interfaces between human monocytes and sintered hydroxylapatite by the use of focused ion beam (FIB) microscopy. The interfaces were examined using energy filtered TEM. © 2007 Springer Science+Business Media, LLC.